Cerebral haemodynamics and long-term prognosis after extracranial-intracranial bypass surgery. Issue 6 (December 1995) - Ishikawa, T; Houkin, K; Abe, H; Isobe, M; Kamiyama, H
Abstract : The effectiveness of extracranial-intracranial arterial (EC-IC) bypass surgery for haemodynamic stroke remains controversial. In this study correlation of presurgical and postsurgical cerebral haemodynamics with long term prognosis was evaluated. Twenty eight patients (25 men, three women: mean age 61.4 (SD 8.2) years) with reduced cerebrovascular reserve due to steno-occlusive cerebral vascular disease formed the study group. Measurement of mean hemispheric cerebral blood flow (mCBF) and the cerebral vasodilatory capacity (% mCVR) with an intravenous acetazolamide injection were performed by a xenon-133 inhalation method and SPECT. Patients were treated with EC-IC bypass surgery and measurements of mCBF and % mCVR were made again about one month after surgery. The patients were then observed for a long period (range 27-115 months). During the observation period, four patients experienced subsequent ischaemic strokes. The presurgical and the postsurgical resting mCBF for the affected hemisphere were significantly reduced in the patients with strokes during follow up compared with the values in patients without strokes during follow up (P < 0.03 and 0.01 respectively). The % mCVR of the affected hemisphere was significantly raised after surgery in all patients except one (P < 0.01). The postsurgical change in resting mCBF was not unidirectional. In conclusion, resting mCBF was unchanged and % mCVR was improved after EC-IC bypass surgery in patients with reduced cerebrovascular reserve. The group of patients with a reduced presurgical and postsurgical resting mCBF continue to be a high risk group for subsequent ischaemic stroke seen after EC-IC bypass surgery.